Comparative Life Expectancy in Africa - McCarthy, F. Desmond (World Bank, Washington, DC, 2014)
For health outcomes, is poverty destiny? The authors explore this question for life expectancy in Africa, where health outcomes are positively correlated with income, but where the link is far from uniform. The key variables associated with good health outcomes (controlling for health expenditures) are access rates - to health services, to clean water and sanitation, and to education, particularly for women. Health expenditure, either as percentage of GNP or per capita, is not a good predictor of health outcomes (endogeneity aside). The tenuous link among health expenditures, health service outputs, and health outcomes suggests marked differences in the mapping from spending to services and from services to outcomes. While few conclusions can be drawn on the aggregate level, the patterns raise questions about what share of public expenditure should be devoted to preventive as opposed to curative measures, and the relative importance of sanitation infrastructure versus traditional health care.